2021
DOI: 10.18502/sjms.v16i2.9295
|View full text |Cite
|
Sign up to set email alerts
|

Feelings, Stress, and Coping of Nurses Amidst COVID-19 Outbreak in Saudi Arabia

Abstract: Background: A year after the COVID-19 pandemic spread around the world, the pandemic is still affecting healthcare systems with an increasing number of infected healthcare workers. Such a unique situation may often result in emotional turmoil, anxiety, depression, and fear, which could lead to resignation and burnout. The study intended to assess the feelings of nurses toward the COVID-19 outbreak; ascertain the factors that cause stress; and determine their coping strategies and factors contributing to coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…The results of this study showed that the majority of critical care nurses reported a moderate to high level of COVID-19-related stress, similar to previous studies ( Rahman et al, 2021 ; Mohsin et al, 2021 ; Alotni & Elgazzar, 2020 ; Crowe et al, 2021 ; Said & El-Shafei, 2020 ; Lu et al, 2020 ). Our study revealed that nurses were severely stressed that “something serious will happen unexpectedly with the epidemic,” which indicates that nurses may have been afraid that they could transmit COVID-19 to a loved one, a fear potentially exacerbated by the insufficient supply of personal protective equipment ( Natividad et al, 2021 ). Also, working at a hospital that hosts COVID-19 patients, regardless of whether or not healthcare workers dealt directly with these COVID-19 patients, was significantly associated with developing anxiety ( Alenazi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of this study showed that the majority of critical care nurses reported a moderate to high level of COVID-19-related stress, similar to previous studies ( Rahman et al, 2021 ; Mohsin et al, 2021 ; Alotni & Elgazzar, 2020 ; Crowe et al, 2021 ; Said & El-Shafei, 2020 ; Lu et al, 2020 ). Our study revealed that nurses were severely stressed that “something serious will happen unexpectedly with the epidemic,” which indicates that nurses may have been afraid that they could transmit COVID-19 to a loved one, a fear potentially exacerbated by the insufficient supply of personal protective equipment ( Natividad et al, 2021 ). Also, working at a hospital that hosts COVID-19 patients, regardless of whether or not healthcare workers dealt directly with these COVID-19 patients, was significantly associated with developing anxiety ( Alenazi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Occupational status, number of family members, and years of experience in the medical sector were all linked to burnout ( AlJhani et al, 2021 ). However, coping mechanisms were found to be more prevalent in those aged 25–34 years, females, married, and those with a bachelor’s degree ( Natividad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This incident corroborates that nurses and other healthcare workers are in the extreme emotional turmoil that requires urgent interventions. In a more recent study, Natividad et al (2021) explored nurses’ feelings and factors that cause stress; and coping strategies during COVID-19. The authors opined that one year after the pandemic outbreak, the healthcare systems are still struggling with an increasing number of infected healthcare workers who are also experiencing emotional harm.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Nurses are the largest number of health care providers and are at the frontline to face COVID‐19 outbreaks (Choi et al, 2020 ). Despite the danger of infection, nurses' dedication to their work appears to be an innate desire to provide care for patients with COVID‐19 (Natividad et al, 2021 ). Nonetheless, the universal effort to control the outbreak leads to higher work hours and workload, which has been defined as the primary contributor to work‐related stress among nurses (Alenezi et al, 2018 ; Duarte et al, 2020 ; Hoedl et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%